Bioindicators of soil quality of open shrubland and vineyards - Vega Avila, Angela Daniela (2018)
Land-use effects on microbial communities may have profound impacts on agricultural productivity and ecosystem sustainability because they are critical to soil quality and health. Within this context, soil microbiological properties such as microorganism abundance, total microbial biomass, and enzymatic activities have been used as soil quality indicators. However, these properties are very sensitive to changes triggered by agronomic management. The aim of this work was to evaluate the effect of agricultural practices in the vineyards from the Central Monte Desert, San Juan, Argentina including the effects on soil microbial biomass using soils from the open shrubland as a reference. The microbial biomass carbon was significantly greater in soils from the open shrubland than in the vineyards during April and November. The abundance of cultivable soil microorganisms (bacteria and filamentous fungi) in soil samples from vineyards and open shrubland was statistically similar. Vineyard soils showed increased enzymatic activities (both in rows and between rows) in both seasons. We used multivariate analysis of all data measured here to propose a data set of variables (amylase, cellulase, and xylanase activities, bacterial abundance, microbial biomass and water content, pH and electric conductivity) for use in future studies of soil quality in the Central Monte Desert